2005
DOI: 10.1007/s10517-005-0330-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapy of Cerebral Palsy

Abstract: The paper presents the results of a controlled study of cell therapy in 30 patients with severe forms of cerebral palsy. A cell suspension from immature nervous and hemopoietic tissues was injected into the subarachnoidal space of a recipient through a spinal puncture. Immune sensitization to donor antigens (detected by suppression of lymphocyte migration) was noted in few patients. In none patients laboratory and clinical signs of tissue-destructive autoimmune reactions were observed. One year after treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…According to our clinical observations, most patients were excited and had difficulty in falling asleep within the first 1–3 days following transplantation, which we attributed to the stimulating effects of neurotrophic factors released by NPCs. Some patients showed improvements within a few days after the surgery, which was consistent with the observations of Chen et al (5) and Seledtsov et al (36) after treating children with CP using olfactory ensheathing cells and fetal brain cells. They reported that most patients had abatement in manifestations within a few days after therapy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to our clinical observations, most patients were excited and had difficulty in falling asleep within the first 1–3 days following transplantation, which we attributed to the stimulating effects of neurotrophic factors released by NPCs. Some patients showed improvements within a few days after the surgery, which was consistent with the observations of Chen et al (5) and Seledtsov et al (36) after treating children with CP using olfactory ensheathing cells and fetal brain cells. They reported that most patients had abatement in manifestations within a few days after therapy.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, the effects of cell transplantation on patients with stroke, Parkinson's disease, and Huntington's disease were apparent much later than in this study (18,22), probably due to the different environments in the brain of the various subjects investigated. The subjects investigated in the present study and in the study by Seledtsov et al (36) were children of nonprogressive brain injury with permanent damage. Because developing brains have stronger plasticity and capability than adult ones, these quick effects were probably due to endogenous neural mechanism that was quickly activated by neurotrophic factors, such as glial cell-derived neurotrophic factor (GDNF), neurotrophin-3 (NT-3), brain-derived neurotrophic factor (BDNF), and neural growth factor (NGF) released by grafted NPCs (10,26,43).…”
Section: Discussionmentioning
confidence: 76%
“…Administration of autologous bone marrow-derived stem cells in patients with subacute and chronic spinal cord injuries has resulted in improvements like changes in ASIA scale as well as electrophysiological changes (6,12,19). In case of cerebral palsy, published data have revealed that cell transplantation in patients suffering from cerebral palsy is found to be safe and showed apparent neurological improvements (10,15,16). For muscular dystrophy, trials have been conducted for transplantation of myoblast cells, mesenchymal stem cells, and umbilical cord stromal cells, proving cell transplantation to be safe and efficacious (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that cell therapy is a safe method and can be effectively used for stroke (308), acute brain injury (346,347), and cerebral palsy (345). In addition, neurological function has been restored after autologous neural stem cell transplantation in patients with brain trauma (428).…”
Section: Clinical Studies Of Cell-based Neurorestoratology In Cns Dismentioning
confidence: 99%